Tailoring In-Flight Food Consumption to Alleviate Fear of Flying Through Sensory Stimulation - Francesco Sansone; Francesca Gorini; Alessandro Tonacci; Francesca Venturi (Applied Sciences, 2025)
Nowadays, society is becoming increasingly committed to traveling by plane for work, tourism, and leisure in general. However, either due to internal, specific factors or to external determinants, like terrorism and climate changes, a growing number of travelers have experienced the so-called fear of flying, a persistent, irrational fear of flight-related situations for which a clear, efficacious therapy does not yet exist. Based on the usual interaction with the surrounding environment, conducted by means of the five human senses, and particularly on the neurophysiological pathway followed by the chemical senses, in this study, we revise the findings in the related literature on the topic, proposing an alternative way to alleviate the anxiety related to the fear of flight. This is based on chemosensory stimulation being applied directly during a flight and is possibly concerned with the consumption of meals, an usual activity performed onboard. After an introductory section aimed at understanding the problem, we present some studies related to chemosensory perception during the flight, highlighting the specificities of the scenarios, followed by a description of findings related to the meals proposed by flight companies in this context, and finally wrapping up the possible alternative approaches that could be conducted by such providers to alleviate the fear of flying condition through chemosensory stimulation vehiculated by meals, and enhance the quality of flight experience related to food consumption onboard.